Comparative investigation on performance of single-stage and double-stage desiccant dehumidification boxes under hot-humid climatic conditions. (February 2023) - He, Fuquan; Yang, Wansheng; Ling, Zipeng
Highlights: A new structure of desiccant fixed bed was proposed and tested. Dehumidification capacity of double-stage box could reach 1.6 gkg −1 on average. Maximum dehumidification efficiency of double-stage box could peak 27.8% in given condition. 97% of the adsorption heat was directed to heat storage of the desiccant. Abstract: Desiccant fixed bed is a prospective alternative for conventional vapor compression refrigeration system. In this paper, a novel structure of fixed bed, desiccant dehumidification box, was constructed and experimented at a sub-tropical city, Guangzhou. Dehumidification performance of the new structure was evaluated by several indicators. Mathematical models were established concerning moisture adsorption rate and moisture ratio. The adsorption heat generated was analyzed by testing sensible heat gain of the process air and heat storage of the desiccant. The result shows that the double-stage desiccant dehumidification box could perform better generally. The maximum dehumidification capacity could reach 3.9 gkg −1 and 1.6 gkg −1 on average in condition 4. Maximum dehumidification efficiency (27.8%) was obtained in the same condition when applying the double-stage box. The desiccant saturated at about 6 h in experiments, of which variation in the double-stage box was more stable and lasting, though moisture adsorption rate presents only a little difference in comparison boxes. Exponential models fit the practical curves within 10% relative error. Maximum average temperature rise of the desiccant and process air was 4.3  °C and 3.8  °C respectively in the double-stage box, which was 0.4  °C and 0.9  °C higher than the single-stage box. Around 97% of the adsorption heat was directed to heat storage of the desiccant and only left 3% directed to sensible heat gain of the process air.